Maternal vitamin D in pregnancy and infant's gut microbiota: a systematic review - Molani-Gol, Roghayeh; Rafraf, Maryam (Frontiers in Pediatrics, 2023)
Background: An infant's gut microbiome has a vital role in their health, and various factors can impact their gut microbiota composition. This review aimed to summarize the current knowledge regarding the associations between maternal prenatal supplementation with vitamin D and the composition of infants' gut microbiota.Method: A comprehensive systematic search was done on Web of Sciences, Scopus, PubMed, ScienceDirect, and Google Scholar databases without date restrictions until December 2022 by relevant keywords. All relevant original articles in English were eligible for the present review.In total, eight articles (two mouse, three randomized clinical trials, and three cohort studies) were included in this review. The included mouse studies reported that maternal prenatal vitamin D supplementation significantly affects the offspring's gut microbiome composition (such as enhancing the abundance of colonic Bacteroides). Moreover, all of the included cohort studies revealed a significant association between maternal supplementation with vitamin D during pregnancy and the infant's gut microbiome. However, one-third of clinical trials indicated that vitamin D levels in utero could influence the colonization of the microbial community in the infant's gut.The findings of this review revealed that maternal vitamin D supplementation during pregnancy was linked to an infant's gut microbiome and could impact their gut microbiota composition. However, more studies are warranted to confirm these results.